(untitled) (Research, Society and Development, 2022)
Chagas disease is an infection caused by the protozoan Trypanosoma cruzi. This pathology has a biphasic clinical course, divided into acute and chronic, in which the second is responsible for 10 to 30% of associated cardiac complications, and among the main forms of cardiovascular involvement, it is worth highlighting the occurrence of Systemic Arterial Hypertension (SAH). Therefore, the aim of this study was to review the literature on the main characteristics involving the relation between Chagas disease and SAH. For this, a search for studies was carried out in the following bibliographic databases: PubMed, STM (Science Translational Medicine) and SciELO (Scientific Electronic Library Online), during the period from September to October 2022. Among the results presented, of the total of the 195 studies found in the databases cited, only 30 were used as sources for this review, 7 of which were original articles and 23 were review articles. These studies are shown in Table 1, prepared by the authors. Although the current literature has few studies regarding this theme, two hypotheses could be raised based on the studies found: the first classifies SAH as a risk factor for Chagas disease, and the second considers it a consequence for chagasic patients who are predisposed to have cardiovascular diseases. However, both consider it a complication of trypanosomiasis.